Analisis Faktor Ergonomi pada UMKM Batik Tradisional Kediri - Hilda Fauziyah; Budhi Setianto; Muh Agus Ainur Rosyid; Oktofa Setia P (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
UMKM Traditional Batik located in Kediri is a batik woven craft area that has been established since the 1950s which processes raw products in the form of threads into semi-finished products in the form of cloth and finished products such as sarongs, batik clothes. The batik production process itself still uses simple tools and the process is done manually without tools and the technology used is a hereditary heritage. The risk of ergonomic hazards in traditional batikÂ  has several working postures when carrying out the process of making traditional batik such as standing, sitting or squatting. For this reason, this study aims to assess ergonomic factors in traditional batik workers at Traditional Batik SMEs. The method used in this research is using SNI 9011:2021. The sample of this research is traditional batik craftsmen in Kediri, totaling 10 respondents. Based on the results of observations on traditional BatikÂ  in Kediri using SNI 9011: 2021, the results showed that the working posture of traditional batik workers was classified as in the medium category. Complaints experienced by batik workers in traditional Batik found that most experienced complaints on the shoulders and back. Traditional Batik owners should make improvements to the ergonomic seating of traditional batik workers according to the body posture of the workers, doing regular stretching.